Vegetation fragment influence over urban climate - Oliveira, Tiago Henrique de; Pimentel, Rejane Magalhães de Mendonça; Galvíncio, Josiclêda Domiciano (Journal of Environmental Analysis and Progress, 2017)
Vegetated areas are important to provide environmental quality for the human population that lives in the neighborhood and to avoid natural disasters, such as erosion processes. The monitoring of forest fragments and green areas in urban environment is important to an efficient management of the vegetation. This study aimed to identify the influence of the vegetation over the urban climate. The Leaf Area Index (LAI), Normalized Difference Water Index (NDWI) and surface temperature were considered to be used to monitoring the air temperature. Different vegetation coverture in distinct areas of a big city, as Recife-PE-Brazil, is responsible for the environmental quality conditions, mainly those related to the air temperature and humidity, providing comfortable conditions for the human population. It is indispensable the monitoring these vegetated areas to optimize the quality life in big cities.